1988
DOI: 10.1111/j.1476-5381.1988.tb11738.x
|View full text |Cite
|
Sign up to set email alerts
|

Fade and tachyphylaxis of gastric acid secretory response to pentagastrin in rat isolated gastric mucosa

Abstract: Gastric acid secretory responses to pentagastrin were characterized in the rat isolated gastric mucosa. In particular, the mechanisms underlying fade, declining response upon continued stimulation, and tachyphylaxis, progressively reduced responses upon repeated stimulation, were investigated. Pentagastrin, 10−9‐10−7m, resulted in concentration‐related increases in acid secretion, with a mean maximum of 2.65 μmolcm−2h−1 in response to pentagastrin, 10−7m. Higher concentrations of pentagastrin produced sub‐maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1996
1996
1996
1996

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
(64 reference statements)
0
1
0
Order By: Relevance
“…It has been suggested that this effect could be due to depletion of mucosal histamine stores (Kasbekar 1972). At least with regard to gastrin, fade and tachyphylaxis are considered to be closely related phenomena (Hirst et al 1988).…”
mentioning
confidence: 99%
“…It has been suggested that this effect could be due to depletion of mucosal histamine stores (Kasbekar 1972). At least with regard to gastrin, fade and tachyphylaxis are considered to be closely related phenomena (Hirst et al 1988).…”
mentioning
confidence: 99%